Battery, battery pack, and vehicle
Patent Information
- Application Number
- CN202610083229.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]然而,相关技术中,极片在高速涂布时,极片表层溶剂快速挥发,形成由表及里的干燥梯度,从而在极片内部产生明显的强对流效应,进而导致极片的剥离力下降,严重影响电池的生产良率、安全性与循环寿命
在本申请的实施例中,电池包括负极极片,负极极片包括负极集流体和设置于负极集流体至少一个表面的活性材料层,活性材料层包括活性物质;活性材料层包括第一活性材料层和第二活性材料层,第一活性材料层设置于负极集流体表面,第二活性材料层设置于第一活性材料层表面;其中,第二活性材料层的保水率大于第一活性材料层的保水率。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application belongs to the field of new energy technology, specifically relating to a battery, a battery pack, and a vehicle. Background Technology
[0002] With the rapid development of new energy vehicles, consumer electronics and energy storage industries, batteries have become the core energy storage device in these fields due to their advantages such as high energy density, high operating voltage and low self-discharge.
[0003] As a core component of a battery, the structural uniformity and interfacial stability of the electrode directly affect the battery's electrochemical performance and long-term reliability.
[0004] However, in related technologies, when the electrode is coated at high speed, the solvent on the surface of the electrode evaporates rapidly, forming a drying gradient from the surface to the inside. This results in a significant strong convection effect inside the electrode, which in turn leads to a decrease in the electrode's peeling force, seriously affecting the battery's production yield, safety, and cycle life. Summary of the Invention
[0005] This application aims to provide a battery, battery pack, and vehicle that solves the problem of how to maintain or even improve the peeling force of the electrode sheets while achieving high-speed coating, thereby improving the safety and cycle life of the battery.
[0006] To solve the above-mentioned technical problems, this application is implemented as follows: In a first aspect, embodiments of this application propose a battery including a negative electrode sheet, the negative electrode sheet including a negative current collector and an active material layer disposed on at least one surface of the negative current collector, the active material layer including an active substance; The active material layer includes a first active material layer and a second active material layer, wherein the first active material layer is disposed on the surface of the negative electrode current collector, and the second active material layer is disposed on the surface of the first active material layer; The water retention rate of the second active material layer is greater than that of the first active material layer.
[0007] Optionally, the second active material layer includes a second water-retaining agent, and the first active material layer includes a first water-retaining agent; The water retention rate of the second water-retaining agent is greater than that of the first water-retaining agent.
[0008] Optionally, the content of the second water-retaining agent in the second active material layer is greater than the content of the first water-retaining agent in the first active material layer.
[0009] Optionally, the difference between the content of the second water-retaining agent in the second active material layer and the content of the first water-retaining agent in the first active material layer is greater than or equal to 0.3%.
[0010] Optionally, the difference between the content of the second water-retaining agent in the second active material layer and the content of the first water-retaining agent in the first active material layer is in the range of 0.3% to 1.5%.
[0011] Optionally, the boiling points of both the first water-retaining agent and the second water-retaining agent are higher than the boiling point of water.
[0012] Optionally, both the first and second water-retaining agents comprise hydrogen-bonded compounds.
[0013] Optionally, the hydrogen-bonded compound includes one or more of polyacrylic acid, polyvinyl alcohol, polyacrylamide, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, 1,3-butanediol, propylene glycol, propylene carbonate, ethylene carbonate, and N-methylpyrrolidone.
[0014] Optionally, the thickness of the negative electrode sheet is the sum of the thickness of the first active material layer and the thickness of the second active material layer, wherein the thickness of the first active material layer accounts for 30-70% of the thickness of the negative electrode sheet.
[0015] Secondly, embodiments of this application propose a battery pack including the battery described above.
[0016] Thirdly, embodiments of this application propose a vehicle including the aforementioned battery pack, wherein the battery pack serves as a power supply for the vehicle.
[0017] Compared with existing technologies, the battery described in this application has the following advantages: In an embodiment of this application, the battery includes a negative electrode sheet, the negative electrode sheet includes a negative current collector and an active material layer disposed on at least one surface of the negative current collector, the active material layer includes an active substance; the active material layer includes a first active material layer and a second active material layer, the first active material layer is disposed on the surface of the negative current collector, and the second active material layer is disposed on the surface of the first active material layer; wherein, the water retention rate of the second active material layer is greater than the water retention rate of the first active material layer.
[0018] By depositing an active material layer on at least one surface of the negative electrode current collector, the active material layer includes a first active material layer and a second active material layer. The first active material layer is deposited on the surface of the negative electrode current collector, and the second active material layer is deposited on the surface of the first active material layer. By controlling the water retention rate of the second active material layer to be greater than that of the first active material layer, the water retention capacity of the second active material layer in the electrode sheet is made superior to that of the first active material layer in the electrode sheet. This balances the drying rates of the second and first active material layers during high-speed coating, reduces the phenomenon of binder floating in the active material layer, and ensures or even improves the peel force of the electrode sheet, thereby improving the production yield, safety, and cycle life of the battery.
[0019] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Detailed Implementation
[0020] The embodiments of this application will now be described in detail, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. All other embodiments obtained by those skilled in the art based on the embodiments of this application without inventive effort are within the scope of protection of this application.
[0021] To meet the growing market demand, battery manufacturers are constantly pursuing capacity expansion. Among these efforts, the coating process in electrode manufacturing is one of the key steps affecting production efficiency and battery performance. Increasing coating speed has become a common trend in the industry to achieve large-scale, high-efficiency production, which places higher demands on electrode preparation processes.
[0022] In the coating process, after the slurry is coated onto the current collector, it needs to be dried in an oven to take shape. During the drying process, the control of parameters such as temperature and air velocity directly affects the distribution of the binder within the electrode and the bonding strength between the active material and the current collector. Currently, to match the high-speed coating production rhythm, the drying of the electrode is usually accelerated by increasing the baking temperature or increasing the air velocity, so as to maintain the overall efficiency of the production line.
[0023] High-temperature or high-wind drying methods used in high-speed coating can lead to rapid evaporation of solvents on the electrode surface, creating a drying gradient from the surface inwards. This results in a significant strong convection effect within the electrode. This effect causes the binder in the slurry to migrate upwards during drying, leading to a relatively higher binder content on the electrode surface and a significantly lower binder content in the lower layers, especially near the current collector. This binder redistribution problem directly weakens the adhesion between the active material layer and the current collector, resulting in decreased electrode peel strength. This, in turn, leads to powder shedding and film delamination during subsequent processes such as slitting and rolling, and exacerbates the risk of separation between the active material and the current collector during battery cycling, severely impacting battery production yield, safety, and cycle life.
[0024] Therefore, how to maintain or even improve the peeling force of the electrode while achieving high-speed coating has become a key technical problem that urgently needs to be solved in this field.
[0025] The present application aims to maintain or even improve the peeling force of the electrode plate while realizing high-speed coating, so as to enhance the safety and cycle life of the battery. In a first aspect, embodiments of the present application provide a battery, which includes a negative electrode plate. The negative electrode plate comprises a negative current collector and an active material layer disposed on at least one surface of the negative current collector, wherein the active material layer includes an active substance; the active material layer includes a first active material layer and a second active material layer, the first active material layer is disposed on the surface of the negative current collector, and the second active material layer is disposed on the surface of the first active material layer; wherein the water retention rate of the second active material layer is greater than the water retention rate of the first active material layer.
[0026] Optionally, in an embodiment, the active substance includes a carbon-based material, and the carbon-based material includes one of graphite, amorphous carbon, and carbon nanomaterials. The graphite includes at least one of natural graphite and artificial graphite; the carbon nanomaterial includes at least one of graphene, graphene oxide, carbon nanotubes, and carbon fibers.
[0027] Optionally, in an embodiment, the active substance includes graphite and silicon, and the silicon includes at least one of silicon-carbon particles, pure silicon particles, and SiO x (0<x<2) particles.
[0028] Optionally, in an embodiment, the active substance may further include one of a tin-based material and a titanium-based material. The tin-based material includes at least one of elemental tin, Sn / C, and SnO2 / C; the titanium-based material includes at least one of lithium titanate (LTO), lithium titanate / graphite composite, and lithium titanate / carbon nanotube composite.
[0029] Optionally, in an embodiment, the active material layer further contains a conductive agent and a binder; the conductive agent includes at least one of conductive graphite, conductive carbon (SP), carbon black, carbon nanotubes, and graphene; the binder includes at least one of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, sodium alginate, and polyvinylidene fluoride.
[0030] In the embodiments of the present application, the active material layer is disposed on at least one surface of the negative current collector, the active material layer includes the first active material layer and the second active material layer, the first active material layer is disposed on the surface of the negative current collector, and the second active material layer is disposed on the surface of the first active material layer; by controlling the water retention rate of the second active material layer to be greater than the water retention rate of the first active material layer, the water retention capacity of the second active material layer in the electrode plate is superior to that of the first active material layer in the electrode plate, so as to balance the drying rates of the second active material layer and the first active material layer during high-speed coating, reduce the phenomenon of binder floating in the active material layer, ensure or even improve the peeling force of the electrode plate, thereby enhancing the production yield, safety and cycle life of the battery.
[0031] Optionally, in one embodiment, the second active material layer includes a second water-retaining agent, and the first active material layer includes a first water-retaining agent; the water retention rate of the second water-retaining agent is greater than that of the first water-retaining agent.
[0032] It should be noted that the first water-retaining agent and the second water-retaining agent can be the same or different. For example, when the first water-retaining agent is 1,3-butanediol, the second water-retaining agent can also be 1,3-butanediol, or N-methylpyrrolidone, etc., as long as the water retention rate of the second water-retaining agent is greater than that of the first water-retaining agent.
[0033] In this embodiment, the second water-retaining agent is located in the second active material layer (surface layer). The high water retention of the second water-retaining agent can lock in the solvent and slow down the convection driving force. The second water-retaining agent has a higher water retention rate and can form a water retention layer on the surface of the electrode, reducing the evaporation rate of the solvent in the second active material layer (surface layer), narrowing the solvent evaporation gradient between the surface layer and the first active material layer (bottom layer), and weakening the upward force of the binder from the source.
[0034] The first water-retaining agent has a relatively low water retention rate, which allows the bottom solvent to evaporate slowly and evenly, avoiding abnormal electrode porosity caused by excessive moisture residue in the bottom layer; at the same time, because the floatation of the binder is suppressed, the interfacial adhesion between the active material layer and the negative electrode current collector is guaranteed, ultimately improving the electrode peeling force.
[0035] Optionally, in one embodiment, the content of the second water-retaining agent in the second active material layer is greater than the content of the first water-retaining agent in the first active material layer.
[0036] It should be noted that the second active material layer is located on the surface layer away from the negative electrode current collector, and the first active material layer is located on the bottom layer close to the negative electrode current collector. When referring to the surface layer and the bottom layer in this application, they can respectively represent the second active material layer (i.e., the surface layer) and the first active material layer (i.e., the bottom layer).
[0037] It should be noted that both the first active material layer and the second active material layer include active substances, water-retaining agents, conductive agents and binders. Based on the mass fraction of the first active material layer and the second active material layer, the content of the second water-retaining agent in the second active material layer is greater than the content of the first water-retaining agent in the first active material layer.
[0038] In this embodiment, the high water-retaining agent content and high water retention rate in the second active material layer can construct a moisture retention barrier, blocking the upward floating force of the binder. The higher content of high water-retaining agent in the second active material layer can form a dense hydrogen bond network on the electrode surface, strongly locking the surface solvent and significantly reducing the difference in solvent evaporation rate between the surface and the bottom layer, directly weakening the convection effect that drives the binder to float. At the same time, the high content of water-retaining agent can synergistically form a film with the surface binder, improving the surface structural strength and avoiding powder shedding problems during subsequent rolling and slitting. More importantly, the binder can maintain the surface structural stability without migrating to the surface, thereby reducing the loss of the bottom binder.
[0039] The low water content and low water retention rate of the first active material layer can ensure the interfacial bonding efficiency. The low content of low water-retaining agent in the first active material layer can achieve slow and uniform evaporation of the bottom solvent, avoiding abnormal electrode porosity caused by water residue. At the same time, because the surface moisture barrier blocks the floating path of the binder, it ensures the interfacial adhesion between the active material, conductive agent and negative electrode current collector, ultimately increasing the electrode peel force to more than 6N / cm (compared to less than 6N / cm for conventional single-layer structures).
[0040] Optionally, in one embodiment, the difference between the content of the second water-retaining agent in the second active material layer and the content of the first water-retaining agent in the first active material layer is greater than or equal to 0.3%.
[0041] It should be noted that the difference between the content of the second water-retaining agent in the second active material layer and the content of the first water-retaining agent in the first active material layer is greater than or equal to 0.3%. For example, the difference between the content of the second water-retaining agent in the second active material layer and the content of the first water-retaining agent in the first active material layer can be one or any two of the following: 0.3%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.6%, 2.0%, and 3.0%.
[0042] In this embodiment, the difference between the content of the second water-retaining agent in the second active material layer and the content of the first water-retaining agent in the first active material layer is greater than or equal to 0.3%. This ensures that the concentration of the water-retaining agent in the surface layer (second active material layer) is sufficient to form a continuous hydrogen bond network, locking in the surface solvent and reducing the difference in solvent evaporation rates between the surface and the bottom layer. Consequently, the convection driving force between the surface and the bottom layer is significantly weakened, thereby reducing the loss of the bottom layer binder and improving the peel strength of the electrode. If the difference is less than 0.3%, the concentration of the surface water-retaining agent is insufficient, and an effective hydrogen bond network cannot be formed. The water-retaining gradient fails, the binder floats to the surface, and the peel strength improvement is not significant.
[0043] Optionally, in one embodiment, the difference between the content of the second water-retaining agent in the second active material layer and the content of the first water-retaining agent in the first active material layer is in the range of 0.3% to 1.5%.
[0044] It should be noted that the difference between the content of the second water-retaining agent in the second active material layer and the content of the first water-retaining agent in the first active material layer ranges from 0.3% to 1.5%. For example, the difference between the content of the second water-retaining agent in the second active material layer and the content of the first water-retaining agent in the first active material layer can be one or any two of the following: 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, and 1.5%.
[0045] In this embodiment, the difference between the content of the second water-retaining agent in the second active material layer and the content of the first water-retaining agent in the first active material layer ranges from 0.3% to 1.5%. The concentration of the water-retaining agent in the second active material layer is sufficient to form a continuous hydrogen bond network, constructing a moisture retention micro-barrier on the surface of the electrode, reducing the evaporation rate of the surface solvent, narrowing the solvent evaporation gradient between the surface and the bottom layer, thereby weakening the convection effect that drives the binder to float. At the same time, it can avoid the negative effects of excessive water retention, balance the water retention effect and the overall performance of the electrode, and maximize the stability of the peel force.
[0046] Optionally, in one embodiment, the boiling points of both the first water-retaining agent and the second water-retaining agent are higher than the boiling point of water.
[0047] It should be noted that the boiling points of the first water-retaining agent, the second water-retaining agent, and water are all boiling points under normal pressure (i.e., standard atmospheric pressure 1.01325 × 10⁻⁶). 5 Boiling point at Pa.
[0048] In this embodiment, the boiling points of both the first and second water-retaining agents are higher than that of water. During coating and drying, water evaporates rapidly, while the first and second water-retaining agents do not evaporate before the water. This ensures that the evaporation rates between the surface and bottom layers are brought closer together during the water evaporation process, thereby reducing the rise of the binder and ensuring a tight bond between the active material layer and the negative electrode current collector interface. This improves the stability of the interface adhesion and enhances the peel strength of the electrode sheet, making it particularly suitable for continuous production under high-speed coating. If the boiling point of the water-retaining agent is lower than that of water (such as low-boiling-point alcohols), the water-retaining agent will boil and evaporate before the water during the drying process. This will not only disrupt the water-retaining gradient but also generate bubbles, leading to defects such as pinholes and cracks on the surface of the electrode sheet. At the same time, the evaporated water-retaining agent vapor will form a gas film at the interface between the bottom layer of the electrode sheet and the negative electrode current collector, hindering the effective contact between the binder and the current collector and significantly reducing the peel strength.
[0049] Optionally, in one embodiment, both the first water-retaining agent and the second water-retaining agent comprise hydrogen-bonded compounds.
[0050] It should be noted that hydrogen-bonded compounds contain polar functional groups such as hydroxyl (-OH), carboxyl (-COOH), and amide (-CONH2).
[0051] In this embodiment, both the first and second water-retaining agents include hydrogen-bonded compounds. The polar functional groups of these compounds can form strong hydrogen bonds with water molecules in the slurry, anchoring free water molecules within the network structure of the electrode active material layer and slowing down the evaporation rate of moisture under high temperature / strong wind conditions in the oven. Simultaneously, the hydrogen-bonded compounds can also construct a three-dimensional network structure to trap and bind water, further delaying moisture evaporation and maintaining the structural integrity of the electrode during the drying process, thus preventing cracking and powdering problems caused by excessively rapid local drying. Due to the water-retaining function of the hydrogen-bonded compounds, the electrode peel strength is ultimately improved by inhibiting the rise of the binder and maintaining the content of the underlying binder.
[0052] Optionally, in one embodiment, the hydrogen-bonded compound includes one or more of polyacrylic acid, polyvinyl alcohol, polyacrylamide, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, 1,3-butanediol, propylene glycol, propylene carbonate, ethylene carbonate, and N-methylpyrrolidone.
[0053] It should be noted that polyacrylic acid, polyvinyl alcohol (PVA), polyacrylamide (PAM), sodium carboxymethyl cellulose (CMC-Na), and lithium carboxymethyl cellulose (CMC-Li) are compounds that act as both hydrogen bond donors and acceptors. Their molecules contain a large number of hydroxyl (-OH), carboxyl (-COOH), and amide (-CONH2) groups, which can both provide active hydrogen to form hydrogen bonds and accept hydrogen bonds through electronegative atoms. This can form a three-dimensional dense hydrogen bond network, firmly anchoring water molecules in the first and second active material layers.
[0054] 1,3-Butanediol, propylene glycol, propylene carbonate, ethylene carbonate, and N-methylpyrrolidone (NMP) are compounds that are only hydrogen bond acceptors. Their molecules contain carbonyl (C=O) and ether (-O-) groups. Although they do not have active hydrogen, their electronegative oxygen atoms can form hydrogen bonds with the hydroxyl groups of water molecules, resulting in a mild water retention effect and a solubilizing effect.
[0055] It should also be noted that the above-mentioned hydrogen-bonded compounds all have boiling points higher than water under normal pressure (or have no boiling point under normal pressure and a decomposition temperature ≥150℃). They will not evaporate or be lost rapidly under oven drying temperature, and can maintain the hydrogen bond water-retaining gradient throughout the process. Even during high-speed coating, the uniformity of electrode drying can still be guaranteed, and the water-retaining agent can be prevented from evaporating, thereby improving the electrode peeling force.
[0056] In this embodiment, the above-mentioned hydrogen-bonded compounds are used as the first and second water-retaining agents to suppress the floating of the binder and improve the peeling force and structural stability of the electrode.
[0057] Optionally, in one embodiment, the thickness of the negative electrode sheet is the sum of the thickness of the first active material layer and the thickness of the second active material layer, wherein the thickness of the first active material layer accounts for 30 to 70% of the thickness of the negative electrode sheet.
[0058] It should be noted that the thickness of the first active material layer accounts for 30% to 70% of the thickness of the negative electrode sheet. For example, the thickness of the first active material layer accounts for one or any two of the following ranges: 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, and 70% of the thickness of the negative electrode sheet. In specific implementation, the thickness of the active material layer is determined by the cell design and can be flexibly adjusted according to actual needs.
[0059] In this embodiment, the thickness of the first active material layer accounts for 30-70% of the thickness of the negative electrode sheet. This ensures the effective bonding area between the first active material layer and the negative electrode current collector, avoiding insufficient peeling force. At the same time, the moisture retention barrier of the second active material layer inhibits the adhesitant from floating, avoiding a decrease in drying efficiency and a degradation of electrochemical performance. Simultaneously, it takes into account both ion transport efficiency and active material loading, achieving synergistic optimization of electrode processing performance and electrochemical performance.
[0060] Alternatively, in one embodiment, the battery further includes a positive electrode and a separator.
[0061] It should be noted that the positive electrode sheet includes a positive current collector and a positive active material layer disposed on the surface of the positive current collector. The positive active material layer includes a positive active material, which includes at least one of nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), and lithium-rich manganese-based materials.
[0062] Optionally, in one embodiment, the nickel-cobalt-manganese / nickel-cobalt-aluminum ternary material includes type 333 (LiNi 0.3 Co 0.3 Mn 0.3 O2), 442 type (LiNi) 0.4 Co 0.4 Mn 0.2 O2), Type 523 (LiNi) 0.5 Co 0.2 Mn 0.3 O2), 622 type (LiNi) 0.6 Co 0.2 Mn 0.2 O2), 811 type (LiNi) 0.8 Co 0.1 Mn 0.1 O2), LiNi 0.9 Co 0.5 Al 0.5 O2, etc.
[0063] Optionally, in one embodiment, the positive electrode further includes a conductive agent and a binder, wherein the conductive agent includes at least one of conductive graphite, conductive carbon, carbon black, carbon nanotubes, and graphene; and the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, and polyvinylidene fluoride-hexafluoropropylene.
[0064] Alternatively, in one embodiment, the battery further includes an electrolyte comprising a lithium salt, a solvent, and additives.
[0065] Optionally, in one embodiment, the lithium salt is selected from one or more of LiPF6, LiFSI, LiTFSI, LiOTf, LiBF4, LiAsF6, and LiClO4.
[0066] Optionally, in one embodiment, the solvent may be selected from one or more of ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and propylene carbonate (PC).
[0067] Optionally, in one embodiment, the additive may be selected from one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl sulfate (DTD), methane disulfonate (MMDS), siloxane additives, lithium bis(oxalate)borate, lithium difluorophosphate, lithium difluorooxalateborate, and lithium nitrate.
[0068] Secondly, embodiments of this application provide a battery pack, which includes the battery described above.
[0069] Thirdly, embodiments of this application provide a vehicle including the aforementioned battery pack, which serves as the vehicle's power supply.
[0070] The battery pack and vehicle embodiments described above include the aforementioned battery and achieve the same technical effects. To avoid repetition, they will not be repeated here. For relevant details, please refer to the description of the battery embodiments.
[0071] To make the inventive objectives, technical solutions, and beneficial effects of this application clearer, the application is further described below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application.
[0072] The present application will be described in detail below through embodiments.
[0073] Test method: Peel force test: Take the cold-pressed negative electrode sheet and cut it into a rectangle of 150mm*20mm. Take a 25mm wide stainless steel plate, apply 20mm wide double-sided tape, and attach the cut negative electrode sheet to the tape. Roll it back and forth three times with a pressure roller to obtain a sample. Fix the prepared sample on a universal tensile testing machine, clamping the stainless steel plate below and the negative electrode sheet above. Under the condition of a testing speed of 100mm / min, perform a 180-degree peel force test to peel the active material layer powder from the negative electrode current collector. Take the average of the three stable values as the peel force F. The electrode adhesion force F1 = F / 0.02.
[0074] Example 1 (1) Preparation of negative electrode sheet Artificial graphite as the negative electrode active material, conductive carbon as the conductive agent, styrene-butadiene rubber as the binder, sodium carboxymethyl cellulose as the thickener and auxiliary binder, and 1,3-butanediol as the first water-retaining agent are mixed in deionized water at a weight ratio of 96.2:1:1.8:1.0:x (where x represents the content of the first water-retaining agent, x is 0.5%) and stirred evenly to form a coating slurry for the first active material layer. Artificial graphite as the negative electrode active material, conductive carbon as the conductive agent, styrene-butadiene rubber as the binder, sodium carboxymethyl cellulose as the thickener and auxiliary binder, and 1,3-butanediol as the second water-retaining agent are mixed in deionized water at a weight ratio of 96.2:1:1.8:1.0:y (where y represents the content of the second water-retaining agent, and y is 2%), and stirred evenly to form a coating slurry for the second active material layer. Copper foil is used as the negative electrode current collector. A coating slurry for the first active material layer is first applied to the negative electrode current collector using a dual-die head to form the first active material layer. Then, a coating slurry for the second active material layer is applied to the surface of the first active material layer to form the second active material layer. The coating is then baked at 120°C for 1 hour, followed by cold pressing, cutting, and slitting to obtain the negative electrode sheet. The thickness of the first active material layer and the thickness of the second active material layer each account for 50% of the thickness of the negative electrode sheet.
[0075] (2) Preparation of positive electrode sheet With LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523) is used as the positive electrode active material, conductive carbon is used as the conductive agent, and polyvinylidene fluoride is used as the binder. They are mixed in N-methylpyrrolidone at a weight ratio of approximately 96:2:2 and stirred evenly to obtain a positive electrode slurry. Aluminum foil is used as the positive electrode current collector. The positive electrode slurry is coated on the surface of the positive electrode current collector and baked at 120°C for 1 hour. Then, it is cold-pressed, cut, and slit to obtain the positive electrode sheet.
[0076] (3) Battery preparation The above-mentioned positive electrode sheet, separator, negative electrode sheet and separator are stacked in sequence, wound up, and the tail tape is attached at the winding point to obtain the bare cell. In an argon atmosphere, ethylene carbonate and methyl ethyl carbonate were mixed at a volume ratio of 3:7, and then lithium hexafluorophosphate was added. The concentration of lithium hexafluorophosphate was 1.0 mol / L to obtain the electrolyte. The bare battery cell is placed into an aluminum casing, dried at 100°C, and then injected with the electrolyte. After vacuum sealing, settling, formation, and shaping, the battery is obtained.
[0077] Example 2 The difference between Example 2 and Example 1 is as follows: In Example 2, the content of the second water-retaining agent y in the preparation of the negative electrode sheet in step (1) was adjusted to 0.8%.
[0078] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0079] Example 3 The difference between Example 3 and Example 1 is as follows: In Example 3, the content of the second water-retaining agent y in the preparation of the negative electrode sheet in step (1) was adjusted to 0.7%.
[0080] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0081] Example 4 The difference between Example 4 and Example 1 is as follows: In Example 4, the content of the second water-retaining agent y in the preparation of the negative electrode sheet in step (1) was adjusted to 2.1%.
[0082] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0083] Example 5 The difference between Example 5 and Example 1 is as follows: In Example 5, in the preparation of the negative electrode sheet in step (1), both the first water-retaining agent and the second water-retaining agent were changed to polyacrylic acid.
[0084] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0085] Example 6 The difference between Example 6 and Example 1 is: In Example 6, in the preparation of the negative electrode sheet in step (1), both the first water-retaining agent and the second water-retaining agent were adjusted to polyacrylic acid, and the content of the second water-retaining agent y was adjusted to 0.8%.
[0086] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0087] Example 7 The difference between Example 7 and Example 1 is as follows: In Example 7, in the preparation of the negative electrode sheet in step (1), both the first water-retaining agent and the second water-retaining agent were adjusted to polyacrylic acid, and the content of the second water-retaining agent y was adjusted to 0.7%.
[0088] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0089] Example 8 The difference between Example 8 and Example 1 is: In Example 8, in the preparation of the negative electrode sheet in step (1), both the first water-retaining agent and the second water-retaining agent were adjusted to polyacrylic acid, and the content of the second water-retaining agent y was adjusted to 2.1%.
[0090] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0091] Example 9 The difference between Example 9 and Example 1 is as follows: In Example 9, in the preparation of the negative electrode sheet in step (1), both the first and second water-retaining agents were adjusted to N-methylpyrrolidone.
[0092] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0093] Example 10 The difference between Example 10 and Example 1 is as follows: In Example 10, in the preparation of the negative electrode sheet in step (1), both the first and second water-retaining agents were adjusted to N-methylpyrrolidone, and the content of the second water-retaining agent y was adjusted to 0.8%.
[0094] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0095] Example 11 The difference between Example 11 and Example 1 is as follows: In Example 11, in the preparation of the negative electrode sheet in step (1), both the first and second water-retaining agents were adjusted to N-methylpyrrolidone, and the content of the second water-retaining agent y was adjusted to 0.7%.
[0096] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0097] Example 12 The difference between Example 12 and Example 1 is as follows: In Example 12, in the preparation of the negative electrode sheet in step (1), both the first and second water-retaining agents were adjusted to N-methylpyrrolidone, and the content of the second water-retaining agent y was adjusted to 2.1%.
[0098] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0099] Example 13 The difference between Example 13 and Example 1 is: In Example 13, the content of the second water-retaining agent y in the preparation of the negative electrode sheet in step (1) was adjusted to 1.4%.
[0100] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0101] Example 14 The difference between Example 14 and Example 1 is: In Example 14, in the preparation of the negative electrode sheet in step (1), the first water-retaining agent was changed to polyvinyl alcohol and the second water-retaining agent was changed to propylene glycol.
[0102] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0103] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is as follows: In Comparative Example 1, no first water-retaining agent or second water-retaining agent was added during the preparation of the negative electrode sheet in step (1).
[0104] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0105] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is as follows: In Comparative Example 2, during the preparation of the negative electrode sheet in step (1), the content of the first water-retaining agent x and the content of the second water-retaining agent y were both adjusted to 1.0%.
[0106] The coating slurry consists of artificial graphite as the negative electrode active material, conductive carbon as the conductive agent, styrene-butadiene rubber as the binder, sodium carboxymethyl cellulose as the thickener and auxiliary binder, and 1,3-butanediol as the first water-retaining agent, mixed in deionized water at a weight ratio of 95.2:1:1.8:1.0:1.0 and stirred evenly to form the first active material layer. Artificial graphite as the negative electrode active material, conductive carbon as the conductive agent, styrene-butadiene rubber as the binder, sodium carboxymethyl cellulose as the thickener and auxiliary binder, and 1,3-butanediol as the second water-retaining agent are mixed in deionized water at a weight ratio of 95.2:1:1.8:1.0:1.0 and stirred evenly to form a coating slurry for the second active material layer.
[0107] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0108] The batteries obtained in each embodiment and comparative example were subjected to peel force tests, and the results are shown in Table 1.
[0109] Table 1
[0110] According to the results in Table 1, whether the first water-retaining agent and the second water-retaining agent are the same or different in the examples, as long as the content of the second water-retaining agent in the second active material layer is greater than the content of the first water-retaining agent in the first active material layer, the water retention rate of the second active material layer can be maintained at a higher level than that of the first active material layer, thereby improving the peeling force of the electrode. Compared with Comparative Examples 1 and 2, Examples 1 to 14 do not contain a water-retaining agent, while Comparative Example 2 contains both the first and second water-retaining agents, but there is no relationship between the water retention rates. The peeling forces of the electrodes obtained in Examples 1 to 14 are all less than or equal to 6 N / m, while the peeling forces of the examples are much greater than 6 N / m. It can be seen that by controlling the water retention rate of the second active material layer to be greater than that of the first active material layer, the peeling force of the electrode can be significantly improved, thereby improving the yield, safety, and cycle performance of the battery.
[0111] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0112] Although embodiments of this application have been shown and described, those skilled in the art will understand that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of this application, the scope of which is defined by the claims and their equivalents.
Claims
1. A battery, characterized in that, The negative electrode includes a negative electrode sheet, the negative electrode sheet including a negative current collector and an active material layer disposed on at least one surface of the negative current collector, the active material layer including an active substance; The active material layer includes a first active material layer and a second active material layer, wherein the first active material layer is disposed on the surface of the negative electrode current collector, and the second active material layer is disposed on the surface of the first active material layer; The water retention rate of the second active material layer is greater than that of the first active material layer.
2. The battery according to claim 1, characterized in that, The second active material layer includes a second water-retaining agent, and the first active material layer includes a first water-retaining agent; The water retention rate of the second water-retaining agent is greater than that of the first water-retaining agent.
3. The battery according to claim 2, characterized in that, The content of the second water-retaining agent in the second active material layer is greater than the content of the first water-retaining agent in the first active material layer.
4. The battery according to claim 2 or 3, characterized in that, The difference between the content of the second water-retaining agent in the second active material layer and the content of the first water-retaining agent in the first active material layer is greater than or equal to 0.3%.
5. The battery according to any one of claims 2 to 4, characterized in that, The difference between the content of the second water-retaining agent in the second active material layer and the content of the first water-retaining agent in the first active material layer ranges from 0.3% to 1.5%.
6. The battery according to any one of claims 2 to 5, characterized in that, The boiling points of both the first and second water-retaining agents are higher than the boiling point of water.
7. The battery according to any one of claims 2 to 5, characterized in that, Both the first and second water-retaining agents contain hydrogen-bonded compounds.
8. The battery according to claim 7, characterized in that, The hydrogen-bonded compounds include one or more of polyacrylic acid, polyvinyl alcohol, polyacrylamide, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, 1,3-butanediol, propylene glycol, propylene carbonate, ethylene carbonate, and N-methylpyrrolidone.
9. The battery according to any one of claims 1 to 8, characterized in that, The thickness of the negative electrode sheet is the sum of the thickness of the first active material layer and the thickness of the second active material layer, wherein the thickness of the first active material layer accounts for 30-70% of the thickness of the negative electrode sheet.
10. A battery pack, characterized in that, Includes the battery as described in any one of claims 1 to 9.
11. A vehicle, characterized in that, Includes the battery pack of claim 10, wherein the battery pack serves as a power supply for the vehicle.
